Clinical efficacy analysis of one-hole split endoscopy surgery versus unilateral biportal endoscopic surgery for degenerative lumbar spondylolisthesis - Abudurezhake, Muhaimaiti; Huang, Yifei; Wang, Hailong; Aili, Gulinuer; Ma, Zhanjun (Frontiers in Surgery, 2026)
ObjectiveTo compare the clinical efficacy of one-hole split endoscopy (OSE) and unilateral biportal endoscopy (UBE) fusion surgery for degenerative lumbar spondylolisthesis (DLS).MethodsA retrospective analysis was conducted on 55 patients with DLS admitted between January 2022 and March 2023, including 27 patients in the OSE group and 28 in the UBE group. Perioperative parameters, complications, Visual Analogue Scale (VAS) scores for back and leg pain, Oswestry Disability Index (ODI), and intervertebral space height were recorded and compared preoperatively and at 1 week, 1 month, and 6 months postoperatively. At the final follow-up, clinical outcomes and fusion status were evaluated using the modified MacNab criteria and Bridwell fusion grading system.ResultsNo significant differences in baseline characteristics were observed between the two groups (P > 0.05). The OSE group demonstrated significantly less intraoperative blood loss (51.25 ± 9.12 mL) and a shorter postoperative hospital stay (3.1 ± 0.8 days) compared to the UBE group (P < 0.05). One case of dural tear occurred in the OSE group, while one dural tear and one symptomatic epidural hematoma occurred in the UBE group; all complications resolved with conservative treatment. The mean follow-up duration was 16.0 ± 3.5 months. VAS scores for back and leg pain, ODI, and intervertebral space height showed significant improvement at all postoperative time points compared to preoperative values in both groups (P < 0.05). At 1 month postoperatively, the OSE group had a significantly lower VAS score for back pain than the UBE group (P < 0.05). No significant intergroup differences were found in other outcome measures at the remaining time points. At the final follow-up, no significant differences were observed in the fusion rate or the excellent-good rate based on the modified MacNab criteria between the two groups.ConclusionBoth OSE and UBE endoscopic fusion techniques for DLS achieve satisfactory mid- to long-term clinical outcomes and reliable interbody fusion. However, the OSE technique offers minimally invasive advantages, including reduced intraoperative blood loss, faster postoperative recovery, and higher perioperative safety, suggesting it may be a promising alternative for the treatment of DLS.